Leishmanicidal and cytotoxic activity of extracts and saponins from Ilex laurina (Aquifoliaceae) (2016)
ABSTRACT: Purpose: To evaluate the leishmanicidal and cytotoxic activity of alcohol and non-alcohol extracts and saponins from Ilex laurina. Methods: Extracts were obtained by percolation with solvents of different polarities: hexane, dichloromethane, ethyl acetate and ethanol. The ethyl acetate extract was subjected to silica gel column chromatography eluting with a step gradient of dichloromethane-methanol. All products were evaluated in vitro for leishmanicidal activity against amastigotes of leishmania panamensis and cytotoxicity on U937 cells. Results: Two saponins were isolated from the ethyl acetate extract. The ethyl acetate extract showed high leishmanicidal activity against intracellular amastigotes of L. panamensis (EC50, 7.5 ± 1.5 µg/mL) and low activity against axenic amastigotes (EC50, 52.8 ±1.6 µg/mL); this extract showed also high cytotoxicity (LC50, 57.7 ± 12.1 µg/mL). Saponin 2 exhibited high activity against intracellular amastigotes (EC50, 5.9 ± 0.5 µg/mL) but also showed high cytotoxicity on U-937 cells (EC50, 25.7 ± 6.1 µg/mL). This compound showed similar leishmanicidal activity and cytotoxicity to meglumine antimoniate and amphotericin B, respectively, drugs currently used for the treatment of leishmaniasis. Conclusions: Based on these results, Ilex laurina is a potential source of compounds that can lead to the development of new therapeutic alternatives against leishmaniasis.